Missive: Fast Application Launch From an Untrusted Buffer Cache - Howell, Jon; Elson, Jeremy; Parno, Bryan; Douceur, John (JD) (Annual Technical Conference, 2014)
The Embassies system turns the web browser model inside out: the client is ultra-minimal, and hence strongly isolates pages and apps; every app carries its own libraries and provides itself OS-like services. A typical Embassies app is 100 MiB of binary code. We have found that the first reaction most people have upon learning of this design is: how can big apps start quickly in such a harsh, mutually-untrusting environment? The key is the observation that, with appropriate system organization, the performance enhancements of a shared buffer cache can be supplied by an untrusted component. The benefits of sharing depend on availability of commonality; this paper measures a hundred diverse applications to show that applications indeed exhibit sufficient commonality to enable fast start, reducing startup data from 64MiB to 1MiB. Exploiting that commonality requires careful packaging and appropriate application of conventional deduplication and incremental start techniques. These enable an untrusted client-side cache to rapidly assemble an app image and transfer it—via IP—to the bootstrapping process. The result is proof that big apps really can start in a few hundred milliseconds from a shared but untrusted buffer cache.